2021
DOI: 10.3389/fgene.2021.770570
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification, Characterization and Function Analysis of Lineage-Specific Genes in the Tea Plant Camellia sinensis

Abstract: Genes that have no homologous sequences with other species are called lineage-specific genes (LSGs), are common in living organisms, and have an important role in the generation of new functions, adaptive evolution and phenotypic alteration of species. Camellia sinensis var. sinensis (CSS) is one of the most widely distributed cultivars for quality green tea production. The rich catechins in tea have antioxidant, free radical elimination, fat loss and cancer prevention potential. To further understand the evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Similarly, 18 OGs were proven to be related to male sterility in watermelon (Citrullus lanatus), and the research also confirmed that 182 OGs were involved in flower development in cucumber (Cucumis sativus), 520 OGs may help with the large fruit size in wax gourd (Benincasa hispida) (Ma et al, 2022). Study showed that 18 CSGs were mainly associated with phenylalanine biosynthesis, biosynthesis of amino acids, pentose phosphate pathway, photosynthesis, and carbon metabolism (Zhao and Ma, 2021). TSGs were proven to be associated with reproductive organ development, and 25 flower-specific TSGs showed specific expression in developing anthers and had an even higher expression level (Ma et al, 2020).…”
Section: Role Of Orphan Genes In Primary Substance Metabolism and Res...mentioning
confidence: 66%
See 2 more Smart Citations
“…Similarly, 18 OGs were proven to be related to male sterility in watermelon (Citrullus lanatus), and the research also confirmed that 182 OGs were involved in flower development in cucumber (Cucumis sativus), 520 OGs may help with the large fruit size in wax gourd (Benincasa hispida) (Ma et al, 2022). Study showed that 18 CSGs were mainly associated with phenylalanine biosynthesis, biosynthesis of amino acids, pentose phosphate pathway, photosynthesis, and carbon metabolism (Zhao and Ma, 2021). TSGs were proven to be associated with reproductive organ development, and 25 flower-specific TSGs showed specific expression in developing anthers and had an even higher expression level (Ma et al, 2020).…”
Section: Role Of Orphan Genes In Primary Substance Metabolism and Res...mentioning
confidence: 66%
“…The rapid accumulation of genomic data on a large variety of plants will allow increasing integrity of identification of OGs. So far the presence of OGs has been reported in many plants or lineages [such as B. rapa (Jiang et al, 2018), A. thaliana (Yang et al, 2009;Lin et al, 2010;Donoghue et al, 2011;Cui et al, 2015), O. sativa (Guo et al, 2007;Yang et al, 2009;Cui et al, 2015;Jin et al, 2019), P. trichocarpa (Yang et al, 2009), V. unguiculata (Li G. et al, 2019), Poaceae (Campbell et al, 2007), Aegiceras corniculatum (Ma et al, 2021), C. sinensis (Xu et al, 2015), Amaranthus hypochondriacus (Cabrales-Orona and Délano-Frier, 2021), Camellia sinensis (Zhao and Ma, 2021), and eight Cucurbitaceae family members (Ma et al, 2022)]. Every sequenced genome contains OGs whose origins are obscure because of the absence of homologs (Blanco-Melo et al, 2016).…”
Section: Orphan Genes Identification and Its Fast Evolving Characteri...mentioning
confidence: 99%
See 1 more Smart Citation
“…BLAST (2.11.0+) [ 26 ] was used to identify OG based on previous studies [ 6 , 27 29 ]. Moso bamboo protein sequences were downloaded from Bamboo GDB [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…With an increasing number of studies on the epigenetic variations and compositional changes of secondary metabolites in tea plants under different experimental conditions (Zhao et al, 2022;Wang et al, 2022;Liao et al, 2022), the omics dataset of Camellia sinensis has also become increasingly extensive. This has led to the use of systems biology approaches on sequencing data hosted on public databases (Tai et al, 2018;Xia et al, 2020;Zhao et al, 2021), such as gene co-expression analysis, becoming a trend in analyzing omics data of Camellia sinensis, providing tea researchers with a more macroscopic and comprehensive perspective. Researchers have further downloaded large-scale transcriptome data of tea plants and created a more systematic and comprehensive co-expression database TeaCoN (http://teacon.wchoda.com) (Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%